PENDIDIKAN AKHLAK DALAM AL-QUR’AN: ANALISIS SURAT AL-HUJURAT AYAT 9-12 MENURUT AS-SA’DI - Banjarnaor, Riadi; Apip, M.; Shofiyyur Rahman Hawary, M.; Akil Fathur Rahman Syah, M.; Agustiar, Agustiar (Jurnal Al-Fatih, 2024)
This study aims to analyze the moral education contained in Surah Al-Hujurat verses 9-12 based on the interpretation of Shaykh As-Sa'di, as well as explore its implications for the formation of individual and societal character. The method applied is a qualitative approach with content analysis, which allows the researcher to delve into the meaning of these verses. The results of the study revealed that basic values such as unity, mutual respect, and avoidance of negative behavior, such as ghibah and prejudice, are very important in strengthening the Islamic ukhuwah. These findings confirm that the application of forgiveness and open-mindedness in daily life can improve relationships between individuals and contribute to the creation of a more harmonious and civilized society. In conclusion, moral education in the Qur'an not only serves as a moral guide, but also as a strong foundation for building positive character and social relationships. This research is expected to be a source of inspiration for Muslims to internalize noble teachings in daily life.